ANALISIS KINERJA KEUANGAN PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK SEBELUM DAN SAAT PANDEMI COVID-19 - Wiralda Yulianti (2022)
This study was conducted with the aim of knowing the differences in the company's financial performance before and during the Covid-19 pandemic. There are four financial performance variables in this study, namely profitability (ROE), liquidity (CR), leverage (DER), and business activity (TATO). The population in this study are transportation and logistics sector companies, totaling 27 companies listed on the Indonesia Stock Exchange in 2019 and 2020. The sampling technique in this study is a saturated sample so that it obtains 60 sample units. The data analysis technique in this study used the paired sample t-test and the Wilcoxon signed rank test, with the help of the SPSS 26 application. The results of this study showed that (1) profitability before and during the Covid-19 pandemic is different, (2) liquidity before and when the Covid-19 pandemic is not different, (3) leverege before and during the Covid-19 pandemic is not different, (4) business activities before and during the Covid-19 pandemic is different.